The modification of the generalized gauss-seidel iteration techniques for absolute value equations - Rashid Ali; Ashfaq Ahmad; Ijaz Ahmad; Asad Ali (Computational Algorithms and Numerical Dimensions)
This paper proposes two modified generalized Gauss-Seidel iteration techniques to determine the Absolute Value Equations (AVEs). Convergence of the new techniques is established under some appropriate conditions lastly; several numerical examples verify the significance of the techniques.